SIMULTANEOUS DETERMINATION OF GLYCERINE AND DEG IN GLYCERINE RAW MATERIAL USING FT-IR SPECTROSCOPY AND MULTIVARIATE CALIBRATION METHODS - OBEIDAT, SAFWAN M.; HAMMOUDEH, AYMAN Y. (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to determine reliably the concentration of Diethylene Glycol (DEG) in glycerine raw material in a simple and rapid manner using Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy coupled with chemometric methods. Methods: for the first time, the current work employs multivariate data analysis tools and FTIR spectroscopy for the simultaneous determination of glycerine and DEG. Binary mixtures of the two substances were prepared and categorized into calibration, validation and test samples. The DEG ratio in these samples ranged from 1 to 30%. The FTIR spectra were recorded for all samples in the range 3700-815 cm-1, and spectral data for each group of samples were used for Principal Component Analysis (PCA), Principal Component Regression (PCR) and Partial Least Square (PLS) applications. Results: In the case of PCA application, a 100% successful discrimination among pure glycerine, DEG and mixed samples was achieved. Semi-quantitative determination of both substances was also possible using PC1 and PC2, accounting for about 99% of the variation in the data set. When using the PCR algorithm, quantitative analysis of the two substances was successfully achieved with an average recovery percent of 98.32±0.19% for glycerine and 99.89±5.7% for DEG. On the other hand, the mean recovery percent values based on the PLS model were 101.37±0.13% and 103.26±3.2% for glycerine and DEG, respectively. Conclusion: Distinguishing pure samples of both analytes was achieved successfully using FTIR spectroscopy and PCA for data analysis. On the other hand, the quantification of DEG in glycerine was very satisfactory upon analyzing the spectroscopic data using PCR and PLS algorithms. FTIR spectroscopy coupled with PCA, PCR and PLS has, thus, been shown to be of great potential to detect the adulteration of glycerine with DEG.